2002
DOI: 10.1159/000057868
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Antibody on the Structure of Glucans

Abstract: Glucosyltransferase (GTF) plays an essential role in the formation of the biofilm known as dental plaque and in the pathogenesis of dental caries. Mutans streptococci produce at least three distinct GTFs (GtfB, C and D), each of which forms a glucan polymer from sucrose. Glucan is a major constituent of plaque biofilm. GTF adsorbed to a surface forms glucans that differ in structure from those formed by the same enzyme in solution. In the present study, activities of GtfB and GtfC in solution or adsorbed on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The levels of GTF B, C, and D in the culture supernatant of S. mutans growing in the presence of apigenin (see experimental design I in Fig. 1) were detected by enzyme-linked immunosorbent assays (ELISA) using polyclonal anti-GTF B, anti-GTF C, and anti-GTF D rabbit sera as described elsewhere (12,16). An ELISA plate was coated with the culture supernatant.…”
Section: Treatment Of Planktonic Cells and Biofilmsmentioning
confidence: 99%
“…The levels of GTF B, C, and D in the culture supernatant of S. mutans growing in the presence of apigenin (see experimental design I in Fig. 1) were detected by enzyme-linked immunosorbent assays (ELISA) using polyclonal anti-GTF B, anti-GTF C, and anti-GTF D rabbit sera as described elsewhere (12,16). An ELISA plate was coated with the culture supernatant.…”
Section: Treatment Of Planktonic Cells and Biofilmsmentioning
confidence: 99%
“…The operon has strong promoter at the top of gtf B. While for grf C, its operon was at the bottom of gtf C. 9 S.mutansgtf B/C enzyme creates pathogenic insoluble glucan because polimer glucose produced by these two enzymes was aggregation mediator for bacteria on dental surface. 10,11 This can contribute to the intensity of thickness and structure integrity of dental plaque which later can form caries.…”
Section: Discussionmentioning
confidence: 99%
“…Kopec et al have recently reported that the enzymatic activity of glucosyltransferase (GTF), produced by mutans streptococci, which induces dental caries via forming of biofi lm known as dental plaque, was enhanced GTF-specifi c IgG (19). In that paper they showed that such enhancement induced by the specifi c IgG was dominantly observed when GTF was expressed on the surface of the bacteria, similar to the urease of H. pylori, and referred that the specifi c IgG may infl uence on the GTF glucan structure, which would impact on the plaque formation via augmentation of the susceptibility to other bacterial components.…”
Section: Figmentioning
confidence: 99%